Foreign ownership, returns to scale and productivity: Evidence from UK manufacturing establishments - Sourafel Girma; Holger Görg (Centre for Economic Policy Research (CEPR), 2002)
This Paper calculates returns to scale (RTS) and productivity growth in UK manufacturing establishments in the electronics and food industries. Our results show that foreign establishments tend to have lower returns to scale than their domestic counterparts. We also examine the effect of the acquisition of a domestic establishment by a foreign owner on returns to scale and productivity growth. We use a matching and difference-in-differences methodology, which allows us to construct a reasonable counterfactual and to determine the post-acquisition changes in RTS and productivity that can be attributed to the incidence of acquisition, rather than to changes in other external conditions. In both sectors, acquisition has a negative effect on RTS, although the effect appears stronger in the food sector. The effect of foreign acquisition on productivity differs between sectors; establishments in the electronics sector experience a reduction in productivity post acquisition, while plants in the food sector increase productivity.
Keywords: F23; L11; 330; Skalenertrag; Produktivität; Eigentümerstruktur; Elektronikindustrie; Nahrungsmittelgewerbe; Großbritannien